The Effects of Body Awareness on Fall-Related Behaviors and Fall Risk in Geriatric Individuals. - Şen, Müşerref Ebru; Özdemir, Filiz; İnceoğlu, Feyza (Physical & Occupational Therapy in Geriatrics, 2025)
Aims: Aging is an inevitable stage in which in addition to physiological and mental changes, perception and awareness decline, and memory functions gradually deteriorate. The aim of this study was to examine the effects of body awareness on fall-related behaviors and fall risk in geriatric individuals. Methods: This cross-sectional study was conducted with 176 individuals over 65 years of age who presented to family health centers. Body awareness (BAQ), fall-related behaviors (FaB) and fall risk (Morse) were examined. Statistical significance was accepted as p < 0.05 in the analyzes. Results: There was a moderate, negative, and statistically significant relationship between the Morse and BAQ scores of the participants (r=-0.576) (p < 0.05). There was a moderate, positive, and statistically significant relationship between the BAQ and FaB scores of the participants (r = 0.235) (p < 0.05). Conclusions: The results showed a significant relationship between body awareness levels and fall-related behaviors and fall risk in geriatric individuals.